1967
DOI: 10.1515/znb-1967-1005
|View full text |Cite
|
Sign up to set email alerts
|

Die Beziehung zwischen Milchsäurekonzentration und Gewebs-pH beim DS-Carcinosarkom der Ratte

Abstract: Correlation of lactate-concentration and H⊕-concentration in tissue of rat DS-carcinosarcoma was tested with an improved method by intravital pH-measuring.After i. v. dosages of glucose the testing was effected by measurement of 24 points equally distributed within the pH-range of about 6.1 — 7.1.Therefrom we compute the acidification factorIn the tested pH-range the factor is practically constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The pH values obtained in skeletal muscle and in the skin of rats are within the range of values reported earlier (range: 7.20-7.59; Voegtlin et al, 1935;Tagashira et al, 1953;Eden et al, 1955;Kahler & Moore, 1962;Gullino et al, 1965;Rauen et al, 1968;Gebert & Friedman, 1973;Dickson & Calderwood, 1979van den Berg et al, 1982;Hinsull et al, 1984;Jain et al, 1984). Since mean pH values in the skeletal muscle of rats higher than those of the arterial blood were reported (Voegtlin et al, 1935;Kahler & Moore, 1962;Rauen et al, 1968;van den Berg et al, 1982), comparative measurements were performed, in which the techniques used for pH measurements by van den Berg et al (1982) and our group were applied to the same animal.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The pH values obtained in skeletal muscle and in the skin of rats are within the range of values reported earlier (range: 7.20-7.59; Voegtlin et al, 1935;Tagashira et al, 1953;Eden et al, 1955;Kahler & Moore, 1962;Gullino et al, 1965;Rauen et al, 1968;Gebert & Friedman, 1973;Dickson & Calderwood, 1979van den Berg et al, 1982;Hinsull et al, 1984;Jain et al, 1984). Since mean pH values in the skeletal muscle of rats higher than those of the arterial blood were reported (Voegtlin et al, 1935;Kahler & Moore, 1962;Rauen et al, 1968;van den Berg et al, 1982), comparative measurements were performed, in which the techniques used for pH measurements by van den Berg et al (1982) and our group were applied to the same animal.…”
Section: Resultssupporting
confidence: 88%
“…Since mean pH values in the skeletal muscle of rats higher than those of the arterial blood were reported (Voegtlin et al, 1935;Kahler & Moore, 1962;Rauen et al, 1968;van den Berg et al, 1982), comparative measurements were performed, in which the techniques used for pH measurements by van den Berg et al (1982) and our group were applied to the same animal. In contrast to the values by van den Berg et al (1982) and in agreement with the values reported here, the mean pH value in the rat subcutis was found to be 7.35 with our electrode and 7.28 using the Philips electrode employed by the Rotterdam Radio-Therapeutic Institute (Wike-Hooley et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation